APOK (Alat Penutup Otomatis Keran) Berbasis IoT Guna Meningkatkan Kemudahan dan Efisiensi Penggunaan Air - Muliadi, Muliadi; Sari, Dessy Ana (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2024)
This research paper discusses the development of the APOK (Automatic Faucet Closing Device) utilizing the Internet of Things (IoT) as a novel approach to enhance the convenience and efficiency of water use. APOK was developed to automatically close the tap when not in use by incorporating motion sensors and voice recognition technology, the results of which will be transmitted via the ESP32 module. Furthermore, this solution allows real-time water use monitoring via a mobile application or web dashboard constructed on the Blynk program, which is compatible with the ESP32 module. By emphasizing water conservation, user comfort, and awareness of the environment, APOK has the potential to contribute to the preservation of water and sustainable resource management. While challenges such as data security and IoT infrastructure availability need to be addressed, APOK implementation presents beneficial changes in how we see and manage our daily water consumption.